let a , b and y be 3 roots of this cubic equation .
a+b+y=-8 ( the sum of roots ) --- 1
aby=-15 ( the product of roots ) --- 2
a=b+y ( one roots is the sum of the other 2 roots ) -- 3
from 1 , b+y=-8-a
substitute into 3 , a=-8-a , a=-4
Then go back to 1 and 2 again .
b+y=-4 -- 4
by=15/4 -- 5
then u can solve the simultaneous equation (4 and 5) to get b and y .
Note that both b and y can be -2.5 and -1.5 but not at the same time . Lets say if you put b=-2.5 , then y has to be -1.5 and vice versa .